Work Meaning and Justice in Gen Z: The Mediating Role of Engagement in Turnover Intention - Hardi, Irham Hudiya; Aryana Satrya (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Turnover intention among Generation Z employees has emerged as a new challenge in human resource management, yet limited research has examined the roles of meaningful work and perceived organizational justice in this context. This study aims to investigate the influence of these two factors on turnover intention, with work engagement as a mediating variable. Using data from 506 Generation Z respondents and analyzed through Covariance-Based Structural Equation Modelling (CB-SEM) with LISREL, the findings reveal that meaningful work unexpectedly increases turnover intention, while perceived organizational justice shows a negative but non-significant effect. Work engagement fully mediates the relationship between both independent variables and turnover intention. These results suggest that work engagement plays a critical role in retaining Gen Z employees even when they perceive their work as meaningful or fair. This study contributes theoretically to the understanding of turnover intention among the emerging Gen Z workforce and offers practical insights for organizations to enhance employee retention by fostering engagement and aligning work meaning with individual values. Future research is recommended to focus on specific industries to strengthen contextual relevance.